Single Crystals of α–LiIO3 Doped with L–arginine and L–nitroarginine - Danghyan, A. A.
One of the essential crystals for technology is the hexagonal modification of lithium iodate (α–LiIO3), which is endowed with nonlinear optical, pyroelectric, piezoelectric, acousto–optic properties. In recent years, a number of research groups studied physical and physiochemical properties of several single crystals (KDP, ADP, BTCA, ZTC) that were grown in the presence of various amino acids (L–alanine, L–glycine, L–arginine, L–lysine, etc.). In all these studies a positive effect on growth process and crystal quality is described for the amino acids being used as dopants in solutions. Based on the promising results of existing studies, in this work the effect of mixtures of the amino acids L–arginine and L–nitroarginine on α–LiIO3 single crystals is presented. Studies of IR spectrum, UV–Vis transmittance, thermal properties and nonlinear optical activity have shown that the optical quality and physicochemical properties of the crystal were improved in the presence of amino acid dopands. Our data indicates that second harmonic generation activity of the crystals of α–LiIO3 grown with L–arginine and L–nitroarginine dopants is 1.2 times higher than that of pure α–LiIO3.
Keywords: Physics